Pembinaan Etika, Interaksi Sosial, dan Kepedulian bagi Pemuda Gereja GKSI Sion melalui Komunitas Inklusif Berdasarkan Filipi 2:3-4 - Putri Sori Ndruru; Denisman Laia; Yublina Kasse (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The cultivation of ethics, social interaction, and care is a fundamental aspect of shaping the character of church youth to live according to Christian values. The youth of GKSI Sion face various modern challenges, such as individualism, a lack of social concern, and declining quality of relationships among congregation members. This article highlights the importance of an inclusive community as an effective framework for character formation, based on the biblical principle in Philippians 2:3–4, which emphasizes humility, selflessness, and prioritizing the interests of others. Through theological and practical approaches, this formation aims to nurture ethics grounded in love, strengthen healthy social interaction, and foster genuine concern for others. The method employed includes literature study, theological reflection, and contextual analysis of the local congregation. Findings indicate that youth nurtured within an inclusive community demonstrate increased empathy, greater involvement in ministry, and stronger social solidarity. The inclusive community not only functions as a learning space but also as a setting for building a firm faith identity relevant to contemporary challenges. Thus, youth formation through this approach may serve as an applicable model for other churches in strengthening the role of young people as agents of social and spiritual transformation. In conclusion, the integration of Philippians 2:3–4 values into inclusive community formation plays a vital role in raising a church generation that is ethical, socially engaged, and genuinely caring toward others.